Highly regioselective ring-opening of epoxides with amines: a metal- and solvent-free protocol for the synthesis of β-amino alcohols. Issue 15 (27th January 2020) - Li, Dong; Wang, Jing; Yu, Shibo; Ye, Silei; Zou, Wenjie; Zhang, Hongbin; Chen, Jingbo
Abstract : We herein report a metal- and solvent-free acetic acid-mediated ring-opening reaction of epoxides with amines. Abstract : We herein report a metal- and solvent-free acetic acid-mediated ring-opening reaction of epoxides with amines. This process provides β-amino alcohols in high yields with excellent regioselectivity. Importantly, this epoxide ring-opening protocol can be used for the introduction of amines in natural products during late-stage transformations.